ASSESSMENT OF PEDAGOGICAL COMPETENCE OF ACADEMIC STAFF: CASE STUDY - Vindača, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The current European guidelines and national priorities for the development of Latvia – to strengthen the teaching, learning and research capacity of higher education institutions and to develop the corresponding skills and competence of academic staff, promoting the excellence of science and higher education. The article will review the issue of pedagogical competence of academic staff (PCAS) in higher education institutions focusing on the primary tenants of its formation and development, offering the definition of PCAS, emphasizing non-teacher trained academic staff (without pedagogical background). As well as contribute to the discussion of PCAS among the experts and professionals of non-pedagogical field, formulating the core elements for the assessment of PCAS in three perspectives: of educators, of students, of higher education institution. The aim of this article is to determine the list of core elements for the assessment of PCAS, analyzing the proposals of 60 experts from Riga Technical University and defining the perspectives of PCAS assessment. This study will help higher education institutions to rethink their strategies for the assessment of academic staff and further perspectives of their development planning.